PEMETAAN LAHAN TEMPAT PEMAKAMAN UMUM DENGAN METODE K-MEANS WILKS’ LAMBDA (Studi Kasus : Pondok Kelapa) - Yoel Haggen Wijaya (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Nowadays, computer technology is evolving especially in image processing . One of example is Mapping land based on texture and color characteristic’s. To obtain a texture value used Haar Wavelet Transformation method. From this method get 7 feature vectors. To get value of color we use Color Moments method. from this method get 9 feature vectors from each image block. From Haar Wavelet transformation method and Color Moments method can divide the data to a cluster. We use K-Means method to divide the data to a cluster. For analyzing the significant of data clustering, we use multivariate analyzing using Wilks’ Lambda. The result will be compared to the governor official regulation 1997.  Based on that clustering, the wide of land which used output image, the wide of land has  19.775 . Key wordsImagery, Color Moment, Remote Sensing, Texture, Wavelet, Wilks' Lamda.